212 Assessment of Left Ventricular Contractile Reserve in Patients with Severe Symptomatic Aortic Stenosis and Preserved Ejection Fraction. (3rd June 2016) - Cabaco, Ana Rita; Aldalati, Omar; Eskandari, Mehdi; Silaschi, Miriam; Alcock, Emma; Byrne, Jonathan; Wendler, Olaf; Monaghan, Mark; Shah, Ajay; MacCarthy, Philip; Dworakowski, Rafal
Abstract : Introduction: Transcatheter aortic valve implantation (TAVI) has become the standard of care for high risk patients. Perioperative deterioration of left ventricular (LV) contractile function was previously demonstrated after surgical aortic valve replacement. Moreover, there is evidence to suggest that patients with severe LV hypertrophy have diminished contractile reserve. We sought to compare the contractile reserve of aortic stenosis (AS) patients to control and heart failure groups utilising a gold standard load-independent technique. Methods: Patients undergoing TAVI under general anesthesia (AS) and control (Ctrl) and heart failure (HF) patients undergoing diagnostic coronary angiography were recruited for invasive pressure-volume loop studies. We measured systolic indices at rest and followed that by assessment of force-frequency relations with atrial pacing. After correction to body surface area, linear mixed model analysis and Friedman test were used to identify differences. Mean values and standard errors are reported. Results: Sixteen (16) patients were in AS group Vs 15 and 12 in Ctrl and HF groups (age in years 84.3 ± 1.5, Vs 59.4 ± 2.2 and 48.5 ± 4.2, p < 0.001; male 8 (50%), Vs 5 (33%) and 8 (66%), p = 0.46, respectively). At rest, ejection fraction (EF) for AS group was 66% ± 4 Vs 64% ± 4, 42% ± 5 for Ctrl and HF respectively (p = 0.006). The maximum first derivative of LV pressure (dP/dtmax ) was 1097 ± 77mmHg/s Vs 1327 ± 63 and 1034 ± 58, p = 0.017. The load-independent parameters included end-systolic pressure volume relationship (ESPVR) for AS 1.85 ± 0.25 mmHg/ml Vs 1.95 ± 0.35, 1.06 ± 0.18 (p = 0.14), Starling Contractile Index (SCI) for AS 7.06 ± 0.9 mmHg/ml/s Vs 7.34 ± 0.9, 4.77 ± 0.6 (p = 0.124) and Preload Recruitable Stroke Work (PRSW) for AS 40 ± 4.2 mmHg/ml Vs 39.6 ± 4.9, 22 ± 3.7 for Ctrl and HF respectively (p = 0.03). With incremental pacing, dP/dtmax was biphasic in AS patients (1097 to 1300 then 1084, p = 0.24) but upsloping in Ctrl cohort (1327 to 1778, p = 0.045) and flat in HF (1034 to 1356, p = 0.19) (Figure 1 ). ESPVR declined steadily in AS patients with incremental pacing unlike the other 2 groups however the changes did not reach statistical significance. SCI response was biphasic in AS (7.7 to 11.9 then 8.1, p = 0.18), upsloping in both Ctrl group (5.6 to 11, p < 0.01) and HF cohort (4.5 to 6.1, p = 0.006) (Figure 2 ). PRSW remained unchanged in all categories with incremental pacing. Conclusion: These data suggest that aortic stenosis patients with preserved EF have diminished contractile reserve, especially during increased heart rate, and may explain why some of these patients have an unfavorable clinical course post TAVI.